First-Year Students’ Research Challenges: Does Watching Videos on Common Struggles affect Students’ Research Self-Efficacy? - Kelly, Savannah L. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – The purpose of this quantitative study was to measure the impact of providing research struggle videos on first-year students’ research self-efficacy. The three-part video series explicated and briefly addressed common first-year roadblocks related to searching, evaluating, and caring about sources. The null hypothesis tested was that students would have similar research self-efficacy scores, regardless of exposure to the video series.Methods – The study was a quasi-experimental, nonequivalent control group design. The population included all 22 sections (N = 359) of First-Year Writing affiliated with the FASTrack Learning Community at the University of Mississippi. Of 22 sections, 12 (N = 212) served as the intervention group exposed to the videos, while the other 10 (N = 147) served as the control group. A research self-efficacy pretest – posttest measure was administered to all students. In addition, all 22 sections, regardless of control or intervention status, received a face-to-face one-shot library instruction session.Results – As a whole, this study failed to reject the null hypothesis. Students exposed to the research struggle videos reported similar research self-efficacy scores as students who were not exposed to the videos. A significant difference, however, did exist between all students’ pretest and posttest scores, suggesting that something else, possibly the in-person library session, did have an impact on students’ research self-efficacy.Conclusion – Although students’ research self-efficacy may have increased due to the presence of an in-person library session, this current research was most interested in evaluating the effect of providing supplemental instruction via struggle videos for first-year students. As this was not substantiated, it is recommended that researchers review the findings and limitations of this current study in order to identify more effective approaches in providing instructional support for first-year students’ research struggles.